Sex-dependent difference in the relationship between thyroid hormones and gallstone disease in euthyroid subjects - Liu, Guoli; Zheng, Xiao; Jia, Yuzhen; Cao, Ping; Jiang, Zhi; Yang, Libo (Medicine (Baltimore), 2023)
The relationship between thyroid dysfunction and gallstone disease (GSD) has been examined by some observational studies. However, evidence about the relationship between thyroid function and GSD among euthyroid subjects was scarce. The aim of this study was to investigate the association between thyroid function and the presence of GSD in a large-sample euthyroid subjects. A total of 5476 euthyroid subjects who underwent health checkup were included. GSD was diagnosed by hepatic ultrasonography. Conventional risk factors for GSD were assessed as well as serum levels of TSH, TT3, TT4 and Log-transformed TT3/TT4 ratio. A total of 4958 subjects were finally included. Levels of TSH, TT3, TT4, and ln (TT3/TT4) were comparable between GSD and non-GSD group (TSH: 1.73 ± 1.07 vs 1.74 ± 1.07 mIU/L, P = .931; TT3: 1.55 ± 0.40 vs 1.54 ± 0.39 ng/mL, P = .797; TT4: 9.37 ± 2.07 vs 9.49 ± 2.06 ug/dL, P = .245, ln (TT3/TT4): −1.80 ± 0.23 vs −1.83 ± 0.23, P = .130, respectively). Multivariate logistic regression analysis among all subjects revealed that the thyroid function parameters did not reach significant difference. Subgroup analyses showed that the relationship between thyroid function and GSD was different according to gender, with negative association for ln (TT3/TT4) and (odds ratio:0.551, 95% CI: 0.306-0.992, P = .047) and positive association for TT4 (odds ratio:1.077, 1 95% CI: .001-1.158, P = .046) in men. None of the thyroid function parameters was significantly associated with GSD in women. Our findings indicated that low levels of TT3-to-TT4 ratio and high levels of TT4 were significantly and independently associated with GSD among euthyroid male subjects, but not female subjects.